Uncertain Programming in Preliminary Design of Technical Systems with Uncertain Parameters - Veresnikov, G.S.; Pankova, L.A.; Pronina, V.A. (Procedia computer science, 2017)
The work is devoted to preliminary design of technical systems with uncertain parameters in absence of statistic. Optimization models with uncertain variables as the uncertain multiobjective programming models of B. Liu are considered. We offer the uncertain programming models with different ranking criteria and present technique of solving problems of uncertain programming. Decision of the preliminary aerodynamic design problem as the problem of uncertain programming are described.